Pengembangan Paket Pelatihan Teknis Pembinaan Kader Institusi Masyarakat Pedesaan/Perkotaan - Reni Dwi Jayanti; Zulfiati Syahrial; Robinson Situmorang (Peneliti.net, 2018)
The research aims to produce a techical training package for family planning counselor (PKB) to increase the competence of cadres of Village Family Planning (IMP). The strudy is research and development (RnD) which adopted 9 from 10 steps of Dick and Carey Model which integrated with Rontree Model considering of: 1) identify instructional goal, 2) conduct instructional analysis, 3) analize learners and contexts, 4) write performance objectives, 5) develop assessment instruments, 6) develop instructional strategy, 7) develop and select instructional materials, consist of planning, preparing for writing and writing and re-writing, 8. Design and conduct formative evaluation of instruction, 9) revise instruction. The research producted are curriculum, manual book of training, printed module, and instructional evaluation.